A sliding hip screw augmented with 2 screws is biomechanically similar to an inverted triad of cannulated screws in repair of a Pauwels type-III fracture. Issue 8 (August 2017) - Kemker, B.; Magone, K.; Owen, J.; Atkinson, P.; Martin, S.; Atkinson, T.
Abstract: Objective: Pauwels III femoral neck fractures are highly unstable. These fractures are commonly treated with three cannulated screws or sliding hip screw (SHS) implants, however high rates of non-union persist. A hybrid SHS construct has recently been proposed. The objective of the study was to compare this construct to the familiar inverted triad of cannulated screws and to a single SHS. Methods: Fourth generation biomechanical femur analogs were used to create a highly repeatable injury model. The hybrid SHS construct contained a SHS with two superior cannulated screws in an inverted triangle configuration. Eight samples for each construct were biomechanically evaluated and the results compared using ANOVA (p < 0.05). Results: The cannulated triad and hybrid SHS provided similar stiffness and fracture gap motion. The single SHS exhibited significantly lower stiffness and larger fracture plane diastasis than either the inverted triangle of cannulated screws or hybrid SHS (p < 0.05). None of the constructs exhibited catastrophic failure during cyclic loading nor under loading up to 2.5 times body weight. Conclusions: The single SHS provided the least stable fracture fixation, while the inverted triad and hybrid SHS constructs were mechanically similar. The fracture repair simulated here illustrates how these repairs have the potential to return near pre-fracture strength in ideal conditions with young, healthy bone. However; in clinical situations where comminution impairs load transfer through the cortices the hybrid SHS may be the most favorable option.